The Costs of Managing an Urban Forest - Francisco Escobedo; Jennifer Seitz (EDIS)
FOR-217, a 4-page fact sheet by Francisco Escobedo and Jennifer Seitz, reviews some of the types of costs associated with urban forests and presents typical financial costs associated with urban forest management in the city of Gainesville, Florida. Includes references. Published by the UF School of Forest Resources and Conservation, July 2009.